ChemInform Abstract: Single‐Layered Ultrasmall Nanoplates of MoS2 Embedded in Carbon Nanofibers with Excellent Electrochemical Performance for Lithium and Sodium Storage. Issue 22 (3rd June 2014) - Zhu, Changbao; Mu, Xiaoke; van Aken, Peter A.; Yu, Yan; Maier, Joachim
Abstract MoS2 single‐layered ultrasmall nanoplates embedded in carbon nanowires are prepared by a scalable electrospinning process using a DMF solution of (NH4)2MoS4 and polyvinylpyrrolidone followed by calcination (alumina crucible, 1.